Quizlet and Vocabulary Mastery: A Case of Indonesian EFL Learners' Reading Comprehension - Fatin Fauziyyah Tiras Putri, - (2019)
Mastering vocabulary is an essential aspect of becoming a proficient language user. However, learning vocabulary yields problems among EFL learners such as low participation, students' difficulties to understand the vocabulary, and difficulties to keep students engaged with lessons being learned. It also affects students' ability to comprehend the text because mastering vocabulary is a basic predictor of reading success. This study, thus, aims to explore the implementation of Quizlet in learning vocabulary and how it assists students' reading comprehension. This study adopted case study design involving tenth-grade students of one public senior high school in Kabupaten Bandung Barat, Indonesia. The data were gained through observation, interview, and test. The data were triangulated to get a portrayal of what occurred during the learning process. The findings indicated that Quizlet to some extent helped students in learning vocabulary through its repetition, enjoyable activities during the learning process, building autonomous learning, encouraging collaboration among the students, as well as a competitive atmosphere that appears during learning, and fostering students' persistence in learning vocabulary. Besides, the result showed that Quizlet can be a vocabulary learning tool as a pre-reading strategy because it assisted the students to prepare unfamiliar vocabulary and promote reading motivation and interest. Therefore, it is suggested that teachers implement Quizlet for vocabulary learning to provide students with a new way of learning that is interesting, innovative, and probably can improve students' learning experience.